Hygienic characteristics of welding methods and welding materials - Levchenko, Oleg; Polukarov, Yury; Zemlyanska, Olena (Kyiv National University of Construction and Architecture, 2025)
The purpose of this work is to assess the hygienic characteristics of various arc welding methods and welding materials and to identify the main factors that affect the degree of risk of hazardous effects of welding aerosol on the body of welders. The assessment methodology was based on the study of the levels of welding aerosol release and its chemical composition depending on the content of components in welding materials that intensify the process of aerosol formation, welding modes and specific properties of the welding methods themselves. The study made it possible to identify welding materials, the use of which is accompanied by the highest levels of welding aerosol release during manual arc welding with covered electrodes, submerged arc welding and mechanized welding. The results obtained make it possible to choose safer welding materials in terms of hygiene for the above-mentioned welding methods. Also, based on the obtained research results, it becomes possible to form substantiated recommendations on the choice of measures and means of protecting welders and auxiliary personnel from harmful factors accompanying welding processes. The novelty of the research lies in the first comprehensive analysis of the hygienic characteristics of arc welding methods and welding materials. Prospects for further research include the development of innovative means of collective and individual protection, as well as the study of the long-term impact of harmful factors on the body of workers. The main limitation is the local nature of the experiments, which requires expanding the scale of the study to confirm the correlation of the results obtained for other welding materials of both domestic and foreign production.